Síntese de celulose bacteriana a partir de resíduos lignocelulósicos via evolução adaptativa - Vasconcellos, Vanessa Molina de (2019)
Bacterial cellulose (BC) is produced mainly by the Komagataeibacter genus. BC is a biopolymer free of impurities, built from the interlacing of cellulose nanofibers, which presents remarkable properties, such as: high mechanical strength, high water retention capacity, susceptibility to chemical modifications and biocompatibility. The BC is a product of great interest in several biotechnological applications, ranging from noble applications, e.g. medical and pharmaceutical fields, to less sophisticated ones, e.g. reinforcement material in polymers. For the BC synthesis is necessary that the culture medium be rich in glucose, one of the key points that increase the final product. In this context, the present thesis aims to contribute to the reduction of costs involved in the process of CB synthesis using as substrate an alternative source of C: the liquid hot water (LHW) pretreated liquid fraction of lignocellulosic wastes (corn stover and sugarcane bagasse) produced in biorefineries. A challenge to be overcome is related to the presence of inhibitors in the medium, and bypassing this barrier with the addition of a detoxification step with activated charcoal, for example, implies an increase in process cost. The alternative presented in this work was to obtain an inhibitor resistant cellulose producing strain through the adaptive laboratory evolution technique, using the HLW pretreated liquid fraction from corn stover as culture medium. The development of the adapted K. hansenii strain makes possible to directly convert, and thereby concentrate, a dilute form of glucose into an insoluble, readily recovered and value-added cellulose product. While genetic stability, its nature and mechanisms behind the synthesis still need to be revealed, the evolutionary adaptation of this nanocellulose-producing bacteria not only made the bacterium resistant to inhibitors but also capable of producing significantly more nanocellulose compared to the original strain. In addition, the nanocellulose of the adapted strain maintained the same properties as those produced in the standard culture medium.